Evaluating the Effectiveness of School Funding and Targeting Different Measures of Student Disadvantage: Evidence from New Zealand1. Issue 303 (15th June 2017) - Clark, Jeremy; Das, Susmita Roy; Menclova, Andrea
Abstract : Many education funding policies seek to lessen the effect of economic disparities outside schools on the disparity of student outcomes within them. A national program for New Zealand schools provides an opportunity to evaluate the effectiveness of government funding in raising graduation rates, and of targeting alternative disadvantage measures. New Zealand targets five deprivation measures: low income, lack of education, low skill employment, crowding, and receiving welfare. Using school fixed effects, we do not find evidence that government funds raise graduation rates for schools, including those serving the most disadvantaged students. We also find no robust evidence that targeting some disadvantage measures is more effective than others. Single parent and rural/urban status are also found to co‐vary significantly with graduation rates.